Application of service MIRO in practical class of Fundamentals of Innovative En-gineering - Natalia N. Shekshaeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper raises the problem of attracting the attention of generation Z (buzzers) to the study of the educational program. The author argues in favor of the use of digital services in education to enhance attention to the subject being studied, as well as the formation of competence - the ability to solve professional problems using information and communication technologies. A list of digital services operating on the territory of the Russian Federation is presented. The analysis of scientific literature in foreign and domestic journals on the use of the MIRO online platform in educational practice is described. The paper is devoted to the presentation of the experience of using the MIRO online platform as a digital learning tool for organizing group and individual work in the study of the discipline "Fundamentals of Innovative Engineering" (FIE) at N. P. Ogarev Mordovian State University in classroom and self-study. The content of the FIE discipline for the specialty Operation of transport and technological machines and complexes" is shown in accordance with the Federal State Educational Standard of higher education. The paper describes the developed set of 9 practical works in MIRO in the discipline Fundamentals of innovative engineering activities which are carried out in the form of a business game A Firm, as well as the experience of performing these works by students. The practice of using MIRO in teaching FIE has shown that the online platform is accessible to teachers and students, the learning materials are easily placed on the platform, and neither students nor teachers had any difficulties in using it. There is a higher interest in performing practical work on FIE in MIRO, in contrast to paper media, and in improving student performance in this discipline. The practical significance of this study lies in the popularization of the use of digital services in the educational process.